Sensitivity of breeding values for carcass traits of meat‐type quail to changes in dietary (methionine + cystine):lysine ratio using reaction norm models. (8th August 2016) - Miranda, J.A.; Pires, A.V.; Abreu, L.R.A.; Mota, L.F.M.; Silva, M.A.; Bonafé, C.M.; Lima, H.J.D.; Martins, P.G.M.A.
Summary: Our objective was to evaluate changes in breeding values for carcass traits of two meat‐type quail ( Coturnix coturnix ) strains (LF1 and LF2) to changes in the dietary (methionine + cystine):lysine ([Met + Cys]:Lys) ratio due to genotype by environment (G × E) interaction via reaction norm. A total of 7000 records of carcass weight and yield were used for analyses. During the initial phase (from hatching to day 21), five diets with increasing (Met + Cys):Lys ratios (0.61, 0.66, 0.71, 0.76 and 0.81), containing 26.1% crude protein and 2900 kcal ME/kg, were evaluated. Analyses were performed using random regression models that included linear functions of sex (fixed effect) and breeding value (random effect) for carcass weight and yield, without and with heterogeneous residual variance adjustment. Both fixed and random effects were modelled using Legendre polynomials of second order. Genetic variance and heritability estimates were affected by both (Met + Cys):Lys ratio and strain. We observed that a G × E interaction was present, with changes in the breeding value ranking. Therefore, genetic evaluation for carcass traits should be performed under the same (Met + Cys):Lys ratio in which quails are raised.